1971
DOI: 10.1128/jvi.7.5.612-618.1971
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Physiological Studies of Bacteriophage T5 I. An Expanded Genetic Map of T5

Abstract: An expanded genetic map of bacteriophage T5 has been constructed by using a set of amber, rather than temperature-sensitive, mutants that represent 29 cistrons. The map consists of three small groups and one large group of genes; mutants defective in genes that are located in different groups exhibit maximal recombination when crossed with one another. However, it has been possible to establish tentative linkage among these groups by use of a particular mutant that appears to affect recombination. One of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

1972
1972
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 17 publications
1
47
0
Order By: Relevance
“…We think that the D7 locus is near the left end of BalI-12. T5D7 also had the highest reversion frequency of the three amber mutants shown, and those with the higher reversion (13) (Fig. 3).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…We think that the D7 locus is near the left end of BalI-12. T5D7 also had the highest reversion frequency of the three amber mutants shown, and those with the higher reversion (13) (Fig. 3).…”
Section: Resultsmentioning
confidence: 85%
“…MATERIALS AND METHODS Strains of bacteria and bacteriophages. The bacteriophage T5 mutants T5D7 (am40c), T5D8 (aml4b), and T5D9 (aml7c) were characterized by Hendrickson and McCorquodale (13). Bacteriophage TSts53 was described previously (9).…”
mentioning
confidence: 99%
“…Preparation and purification of phages T5stamN5 (T5) phages were produced on E.coli Fsuf+, a permissive host (Hendrickson and McCorquodale, 1971;Zweig and Cummings, 1973). Phage 180 was propagated in E.coli K12.…”
Section: Methodsmentioning
confidence: 99%
“…Szabo et al (19) have provided some evidence supporting the proposal of Chinnadurai and McCorquodale (4) that the C2 gene product is a phage "sigma-like" factor, which, as a consequence of binding to Escherichia coli RNA polymerase, permits the host enzyme to recognize the late class of T5 DNA promoters. The gene D15 product is known to be a nuclease (6,9). Enzymatic studies of partially purified D15 nuclease have shown that the protein possesses 5'-*3' exonuclease activity on both singleand double-stranded DNA (6,14).…”
mentioning
confidence: 99%
“…Single amber mutants of T5+ in either gene C2 (T5C2amM142a) or gene D15 (T5D15amH50) were provided by D. J. Mc-Corquodale. The protein products produced by phage genes D15 and C2 are thought to be a nuclease (6,9) and a "a" factor, which interacts with E. coli RNA polymerase (4,19), respectively.…”
mentioning
confidence: 99%